Clinical trials in complementary and alternative medicine – the myth of limitations - Rzepiński, Tomasz; Tabaczewski, Piotr (Journal of Medical Science, 2016)
The paper aims to dispute common arguments put forward by practitioners of complementary and alternative medicine (CAM) in discussions against conducting clinical trials in CAM treatment protocols. It is argued that CAM therapies cannot be evaluated by the same criteria as those applied in conventional medicine due to specificity of CAM. This paper suggests that this line of thought undermines not only the validity of CAM therapies, but, importantly, is delaying understanding their therapeutical value. We also argue that despite apparent differences in approach both conventional medicine and CAM aim to improve human well being therefore CAM should be validated with well established and widely accepted process of balancing of risks and benefits of individual therapies as in conventional medicine clinical trials.